Virtual Screening for the Development of New Effective Compounds Against Staphylococcus aureus - Diniz, Roseane C.; Soares, Lucas Weba; Nascimento da Silva, Luís Cláudio (Current Medicinal Chemistry, 2018)
Staphylococcus aureus is a notorious pathogenic bacterium causing a wide range of diseases from soft-tissue contamination, to more serious and deep-seated infections. This species is highlighted by its ability to express several kinds of virulence factors and to acquire genes related to drug resistance. Target this number of factors to design any drug is not an easy task. In this review, we discuss the importance of computational methods to impulse the development of new drugs against S. aureus. The application of docking methods to screen large libraries of natural or synthetic compounds and to provide insights into action mechanisms is demonstrated. Particularly, the studies that validated in silico results with biochemical and microbiological assays are highlighted. We also comment on the computer-aided design of new molecules using some known inhibitors. The confirmation of in silico results with biochemical and microbiological assays allowed the identification of lead molecules that could be used for drug design such as rhodomyrtone, quinuclidine, berberine (and their derivative compounds). The fast development of the computational methods is essential to improve our ability to discover new drugs, as well as to expand understanding about drug-target interactions.
Keywords: antimicrobials